2014
DOI: 10.3109/00952990.2014.939755
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity in the non-medical use of prescription medication in college students

Abstract: These results extend past research demonstrating that religiosity is protective against substance abuse/misuse. Greek status appears to negate the protective influence of religiosity on NMUPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
3
0
3
Order By: Relevance
“…The present study showed that a high level of religiosity is a protective factor for alcohol abuse. Other studies have shown that subjects with higher levels of religiosity tend to have a more orderly life and behave more prudently [66,67]. Some authors have explained this effect as being due to the influence of peers, as well as the control/protection exercised by the religious community [68].…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that a high level of religiosity is a protective factor for alcohol abuse. Other studies have shown that subjects with higher levels of religiosity tend to have a more orderly life and behave more prudently [66,67]. Some authors have explained this effect as being due to the influence of peers, as well as the control/protection exercised by the religious community [68].…”
Section: Discussionmentioning
confidence: 99%
“…Across the population, white/non-Latino/a individuals have elevated tranquilizer/sedative or benzodiazepine misuse, with inconsistent findings for sex differences. 29,165,127,128 Consistently, though, those engaged in tranquilizer/sedative or benzodiazepine PDM have higher rates of other problematic substance use and SUD, psychopathology and suicidality. 17,106,107,116,124,129-131,162,165 Adolescents, those not in school, those living in socially disorganized neighborhoods, and those with delinquent behavior have higher rates of tranquilizer/sedative PDM.…”
Section: Prescription Tranquilizer/sedative and Benzodiazepine Misusementioning
confidence: 96%
“…O uso não médico por pessoas do mesmo grupo social também foi descrito como um fator de influência, pois conforme a teoria do aprendizado social, indivíduos aprendem a lidar com dificuldades por meio da observação de respostas de amigos e familiares a mesma categoria de problema (Peralta & Steele, 2010). E por fim, praticar religião (Snipes et al, 2014) e ser proveniente de família com renda satisfatória funcionam como fatores protetores, pois se acredita que, para alunos com dificuldades financeiras, o uso de psicofármacos sirva como substituto ao cuidado profissional devido à dificuldade de acesso (Pagán et al, 2006).…”
Section: Discussionunclassified
“…Em relação à diferença de consumo entre os sexos parece haver pouca discordância na literatura sobre a preponderância pelo sexo feminino (Cabrita et al, 2004;Peralta & Steele, 2010). Foi encontrado somente um artigo que referiu maiores taxas pelo sexo masculino, mas mesmo assim, posteriormente o autor ponderou não existir influência pelo sexo (Snipes et al, 2014).…”
Section: Discussionunclassified